Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the expression [tex]\(\sqrt{-98}\)[/tex], we need to follow a series of steps that involve understanding the properties of square roots and imaginary numbers.
1. Identifying the Imaginary Unit:
We know that [tex]\(\sqrt{-1} = i\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
2. Separating the Components:
Given the expression [tex]\(\sqrt{-98}\)[/tex], we can rewrite it as:
[tex]\[ \sqrt{-98} = \sqrt{98} \cdot \sqrt{-1} = \sqrt{98} \cdot i \][/tex]
3. Simplifying the Square Root of 98:
Next, let's simplify [tex]\(\sqrt{98}\)[/tex]. We need to break this down into its prime factors:
[tex]\[ 98 = 2 \times 49 = 2 \times 7^2 \][/tex]
Therefore,
[tex]\[ \sqrt{98} = \sqrt{2 \times 7^2} \][/tex]
4. Using the Property of Square Roots:
We can further simplify using the property [tex]\(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{98} = \sqrt{2 \times 7^2} = \sqrt{2} \times \sqrt{7^2} = \sqrt{2} \times 7 \][/tex]
5. Combining with the Imaginary Unit:
Substituting this back into our expression:
[tex]\[ \sqrt{-98} = \sqrt{98} \cdot i = 7 \sqrt{2} \cdot i = 7i\sqrt{2} \][/tex]
Thus, the expression [tex]\(\sqrt{-98}\)[/tex] simplifies to [tex]\(7i\sqrt{2}\)[/tex].
Therefore, the correct option is:
[tex]\[ \boxed{7i\sqrt{2}} \][/tex]
So the answer is C: [tex]\(7 i \sqrt{2}\)[/tex].
1. Identifying the Imaginary Unit:
We know that [tex]\(\sqrt{-1} = i\)[/tex], where [tex]\(i\)[/tex] is the imaginary unit.
2. Separating the Components:
Given the expression [tex]\(\sqrt{-98}\)[/tex], we can rewrite it as:
[tex]\[ \sqrt{-98} = \sqrt{98} \cdot \sqrt{-1} = \sqrt{98} \cdot i \][/tex]
3. Simplifying the Square Root of 98:
Next, let's simplify [tex]\(\sqrt{98}\)[/tex]. We need to break this down into its prime factors:
[tex]\[ 98 = 2 \times 49 = 2 \times 7^2 \][/tex]
Therefore,
[tex]\[ \sqrt{98} = \sqrt{2 \times 7^2} \][/tex]
4. Using the Property of Square Roots:
We can further simplify using the property [tex]\(\sqrt{a \times b} = \sqrt{a} \times \sqrt{b}\)[/tex]:
[tex]\[ \sqrt{98} = \sqrt{2 \times 7^2} = \sqrt{2} \times \sqrt{7^2} = \sqrt{2} \times 7 \][/tex]
5. Combining with the Imaginary Unit:
Substituting this back into our expression:
[tex]\[ \sqrt{-98} = \sqrt{98} \cdot i = 7 \sqrt{2} \cdot i = 7i\sqrt{2} \][/tex]
Thus, the expression [tex]\(\sqrt{-98}\)[/tex] simplifies to [tex]\(7i\sqrt{2}\)[/tex].
Therefore, the correct option is:
[tex]\[ \boxed{7i\sqrt{2}} \][/tex]
So the answer is C: [tex]\(7 i \sqrt{2}\)[/tex].
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.